Poèmes sociaux - Bouchor, Maurice; Fabry, Camille (Bruxelles : L'Églantine, 1925)
Deze brochure bevat volgende gedichten
L' eau et de vin
Le pain
La muse et l'ouvrier
Fonds Perrone
Frans
Brochure
Keywords: poëzie